2013
DOI: 10.5005/jp-journals-10006-1239
|View full text |Cite
|
Sign up to set email alerts
|

Weight does Matter! A Study of Effect of Obesity on Pregnancy and its Outcome

Abstract: Objectives: To analyze the significant risk associated with obesity and its consequences on obstetrics management and perinatal outcome. Materials and methods:A prospective study was carried out in the Department of Obstetric and Gynecology, MGM Medical College and My Hospital, Indore. The study enrolled 200 pregnant women with body mass index (BMI) >25 and equal number of women with normal BMI (18-24.9) as control.Results: A total of 76 (38%) out of 200 pregnant women were overweight, 70 (35%) were obese type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 9 publications
4
4
0
Order By: Relevance
“…This frequency was almost 5.16 times higher. Our study correlated with many studies by Deve A et al [7], Heather E. Robinson et al [8] and Ramos et al [1] who reported an incidence of 18.9 -22.6% and 16% respectively.…”
Section: Hypertensive Disorders Complicating Pregnancysupporting
confidence: 92%
See 4 more Smart Citations
“…This frequency was almost 5.16 times higher. Our study correlated with many studies by Deve A et al [7], Heather E. Robinson et al [8] and Ramos et al [1] who reported an incidence of 18.9 -22.6% and 16% respectively.…”
Section: Hypertensive Disorders Complicating Pregnancysupporting
confidence: 92%
“…We observed that, labour induction was more in obese group (26.6%). When compared to control group (4.98%), which is in accordance with other studies [5,7]. The risk of induction among the obese women was increased almost 5.3 fold.…”
Section: Induction Of Laboursupporting
confidence: 92%
See 3 more Smart Citations